Validation of the interdisciplinary construct of rice quality in Asia - CGIAR Research Program on Rice (2019)
The interdisciplinary construct of rice quality was validated through a "stacked" value chain survey in seven countries in South and Southeast Asia. Results have been published in Global Food Security, PlosONE, Trends in Food Science and Technology, British Food Journal and Journal of Agribusiness in Developing and Emerging Economies.